2005
DOI: 10.1111/j.1365-2052.2004.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of 0.4 megabases of the rabbit germline immunoglobulin kappa1 light chain locus

Abstract: Two rabbit germline bacterial artificial chromosome (BAC) libraries from animals with the b5 and b4 allotype were screened with probes specific for the immunoglobulin kappa1 light chain locus. Two partially overlapping BAC clones containing Vkappa elements of b5 allotype were isolated from the b5 library and one BAC clone containing Jkappa1, Ckappa and Vkappa was isolated from the b4 library. These three BAC clones were sequenced. They span about 0.4 MB of the rabbit Ig kappa1 light chain locus including 36 Vk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Also, more than 50 IG Kappa V and 17 IG Lambda V functional genes were identified with genomic sequencing (IMGT database). The diversity of rabbit VH repertoire is more limited, and the V light (VL) repertoire is more diverse than that in mice and humans (1720). Most rabbit antibodies are derived from the IGHV1 gene (21).…”
Section: The Rabbit Antibody Repertoirementioning
confidence: 99%
“…Also, more than 50 IG Kappa V and 17 IG Lambda V functional genes were identified with genomic sequencing (IMGT database). The diversity of rabbit VH repertoire is more limited, and the V light (VL) repertoire is more diverse than that in mice and humans (1720). Most rabbit antibodies are derived from the IGHV1 gene (21).…”
Section: The Rabbit Antibody Repertoirementioning
confidence: 99%
“…Second, studies have suggested that the rabbit immune system is more similar to the immune systems of primates and humans than to that of mice (2)(3)(4)(5). Third, rabbit immunoglobulin loci have been well characterized and are relatively simple (1,6,7). In addition, rabbits can produce antibodies with a long complementarity-determining region (CDR) 3 in the heavy chain or CDR H3 (5), a property often found in potent human anti-HIV gp120 MAbs (8).…”
mentioning
confidence: 99%
“…In OryCun2.0, the IGKC1 region is located at 98.92 Mb on the forward strand of chromosome 2. Part of the IGKV and IGKJ region associated with IGKC1 was sequenced by Ros et al (2005) (Figure 3b). The IGKC2 region is also found on assembled chromosome 2, at 98.22 Mb, but in the opposite transcriptional orientation (negative strand).…”
Section: Resultsmentioning
confidence: 99%
“…To search for BACs derived from the IGH, IGK , or IGL regions among the BAC clones in the BAC Library of the Children's Hospital Oakland Research Institute (CHORI) LBNL-1: White Rabbit (Oryctolagus cuniculus) http://bacpac.chori.org/library.php?id=159; (Ros et al 2004, 2005), we used MegaBLAST to search traces created by the Broad Institute by partial sequencing of BACs from the CHORI library. The Broad Institute deposited these O.cuniculus traces from the CHORI library in NCBI's Trace Archive with the “center_project” attribute set to G1348.…”
Section: Methodsmentioning
confidence: 99%